Indications, durations and outcomes of mechanical ventilation in dogs and cats with tick paralysis caused by Ixodes holocyclus: 61 cases (2008–2011). Issue 6 (29th May 2013) - Webster, RA; Mills, PC; Morton, JM
<x xml:space="preserve">Abstract</x> Objectives The primary objectives of this research were to describe the indications for mechanical ventilation, the duration of mechanical ventilation and probability of survival in dogs and cats with respiratory failure induced by the Australian paralysis tick (Ixodes holocyclus). Methods A retrospective case series and a retrospective single cohort study were conducted using dogs and cats with tick paralysis requiring mechanical ventilation. An index of oxygenating performance of the lung (PF ratio of partial pressure of oxygen in arterial blood to fraction of inspired oxygen) was derived from arterial blood gas analysis; patients euthanased because of veterinary costs were identified and Kaplan‐Meier survival analyses performed. Results In total, 36.6% of patients were ventilated because of hypoxaemia refractory to oxygen therapy, 38.3% because of hypoventilation, 18.3% because of unsustainable respiratory effort and 6.6% because of respiratory arrest. Median duration of mechanical ventilation was 23 h, median time hospitalised was 84 h and 63.9% of all patients requiring mechanical ventilation survived to discharge from the hospital. Survival probability increased to 75% when cases of cost‐based euthanasia were right‐censored rather than treated as deaths. The survival probability of patients ventilated because of hypoxaemia (52.6%) was significantly less than for those ventilated because of hypoventilation (90.5%). The first measured PF ratio after commencing mechanical ventilation was not significantly associated with survival probability. Conclusions Dogs and cats with tick paralysis requiring mechanical ventilation to manage respiratory failure have reasonable survival probability. Dogs and cats requiring mechanical ventilation because of hypoventilation have a higher survival probability than those with oxygenation failure.